Total Splenectomy due to an Unexpected "Complication" after Successful Extended Laparoscopic Partial Decapsulation of a Giant Epidermoid Splenic Cyst: A Case Report. (31st May 2011) - Pitiakoudis, Michail; Zezos, Petros; Oikonomou, Anastasia; Laftsidis, Prodromos; Kouklakis, Georgios; Simopoulos, Constantinos
Abstract : Splenic cysts are rare entities and are classified as true cysts or pseudocysts based on the presence of an epithelial lining. Congenital nonparasitic true cysts can be epidermoid, dermoid, or endodermoid, present at a young age, and are commonly located in the upper pole of the spleen. Surgical treatment is recommended for symptomatic, large (more than 5 cm), or complicated cysts. Depending on cyst number, location, relation to hilus, and the major splenic vessels, the surgical options include aspiration, marsupialization, cystectomy, partial cystectomy (decapsulation), and partial or complete splenectomy. Laparoscopic techniques have now become the standard approach for many conditions, including the splenic cysts, with emphasis on the spleen-preserving minimally invasive operations. We present the successful extended partial laparoscopic decapsulation of a giant epidermoid splenic cyst in a young female patient that, although asymptomatic, was unfortunately followed by complete splenectomy five days later due to a misinterpreted abdominal CT suggesting splenic postoperative ischemia.